Decreased Reactive Oxygen Species Production in Cells with Mitochondrial Haplogroups Associated with Longevity - Chen, Ai (Public Library of Science, 2012)
Mitochondrial DNA (mtDNA) is highly polymorphic, and its variations in humans may contribute to individual differences in function. Zhang and colleagues found a strikingly higher frequency of a C150T transition in the D-loop of mtDNA from centenarians and twins of an Italian population, and also demonstrated that this base substitution causes a remodeling of the mtDNA 151 replication origin in human leukocytes and fibroblasts [1]. The C150T transition is a polymorphism associated with several haplogroups. To determine whether haplogroups that carry the C150T transition display any phenotype that may be advantageous for longevity, we analyzed cybrids carrying or not the C150T transition. These cybrids were obtained by fusing cytoplasts derived from human fibroblasts with human mtDNA-less cells (ρ(0) cells). We chose for cybrid construction and analysis haplogroup-matched pairs of fibroblast strains containing or not the C150T transition. In particular, we used, as one pair of mtDNA donors, a fibroblast strain of the U3a haplogroup, carrying the C150T transition and a strain of the U-K2 haplogroup, without the C150T transition, and as another pair, fibroblasts of the J2b haplogroup, carrying the C150T transition and of the J1c haplogroup, without the C150T transition. We have found no association of respiratory capacity, mtDNA level, mitochondrial gene expression level, or growth rate with the presence of the C150T transition. However, we have found that the cybrids with haplogroups that include the C150T transition have in common a lower reactive oxygen species (ROS) production rate than the haplogroup-matched cybrids without that transition. Thus, the lower ROS production rate may be a factor in the increased longevity associated with the U and the J2 haplogroups. Of further interest, we found that cybrids with the U3a haplogroup exhibited a higher respiration rate than the other cybrids examined.